2012
DOI: 10.1371/journal.pone.0041669
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Histological Oligodendroglial Tumor Component: Clinicopathological Analysis of 111 Cases of Malignant Gliomas

Abstract: The favorable prognosis of high-grade oligodendroglial tumor such as glioblastoma (GBM) with oligodendroglioma component (GBMO) has been suggested; however, the studies which examine the prognostic significance of oligodendroglial tumor were limited. In this study, we performed a histopathology-based reevaluation of 111 cases of high grade gliomas according to the latest World Health Organization (WHO), and compared the clinical outcomes between oligodendroglial tumors and pure astrocytic tumors. The survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…The median OS and RFS of the histological subgroups and the AGs as a group in our study is consistent with published literature;5 25 32 38 however, some studies have shown better prognosis in AOs 3 6 32 37 39. Analysis of biomarker expression expectedly revealed p53 positivity and ATRX loss to be associated with AAs (p<0.001) and 1p/19q codeletion to be associated with AOs (p<0.001), whereas IDH1- R132H positivity and m MGMT did not show significant association with the histological subgroups of AG, which is consistent with the current understanding that IDH1- R132H mutations are believed to constitute one of the earliest step in tumorigenesis followed by either p53 mutations/ ATRX loss or 1p/19q codeletion which are believed to drive differentiation towards an AA or AO phenotype, respectively, with MGMT promoter methylation being an epigenetic event 15 16 20 21 25 40–42…”
Section: Discussionsupporting
confidence: 91%
“…The median OS and RFS of the histological subgroups and the AGs as a group in our study is consistent with published literature;5 25 32 38 however, some studies have shown better prognosis in AOs 3 6 32 37 39. Analysis of biomarker expression expectedly revealed p53 positivity and ATRX loss to be associated with AAs (p<0.001) and 1p/19q codeletion to be associated with AOs (p<0.001), whereas IDH1- R132H positivity and m MGMT did not show significant association with the histological subgroups of AG, which is consistent with the current understanding that IDH1- R132H mutations are believed to constitute one of the earliest step in tumorigenesis followed by either p53 mutations/ ATRX loss or 1p/19q codeletion which are believed to drive differentiation towards an AA or AO phenotype, respectively, with MGMT promoter methylation being an epigenetic event 15 16 20 21 25 40–42…”
Section: Discussionsupporting
confidence: 91%
“…This depends on many important things about the histopathological examination that is mainly associated with the high accuracy in the diagnosis of cancer as with breast cancer (95.4%) and other types of malignant diseases such as high-grade gliomas 10 . Meanwhile, the examination revealed more significant diagnostic results for many cancers compared with other methods as with a mammography screening for breast cancer 7 or with other laboratory techniques like light-based detection and oral spectroscopy 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The first one is the accuracy in detection of cancer compared with that obtained with other methods 4,[6][7]10 and the ability to differentiate between benign and malignant disease 18,25 . Furthermore, the assistance of other methods for detection of cancer is another benefit of histopathological examination as it increases the sensitivity of PSA in the detection of the prostate cancer 26 or preliminary diagnosis of basal cell carcinoma based on the appearance 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some of the studies which quoted higher incidence of GBM-O, may have included mixed oligoastrocytomas with necrosis. [4] In the current study, we analysed only those patients whose histopathology was confirmed to be GBM-O based on the above defined criteria. We excluded 4 patients who had secondary GBM so as not to skew our results as they have been reported to contain oligodendroglial component in a relatively high proportion (approximately 40%) [15] and considered as a separate entity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a better survival in GBM-O patients with a median survival of 17-26 months . [4][5][6] while others have failed to demonstrate any survival advantage over unselected GBM [7,8]. The rarity of these tumors and heterogeneity in the chemotherapeutic regimens used has resulted in lack of standard consensus guidelines regarding its management [4,[9][10][11] which is in contrast to GBM where the management guidelines have become uniform following EORTC/NCIC intergroup study and our experience [12,13].…”
Section: Introductionmentioning
confidence: 94%